A práxis e as representações ideológicas do General Jayme Portella: a 'linha-dura' no cenário político brasileiro (1964-1969) - Guerra, Tiago Cavalcante (2008)
This research aims to examine a central figure in the military dictatorship in Brazil and "engineer" of the candidacy and the government by Costa e Silva: the general Jayme Portella. From the study of his writings, noting the historical and social conditions of production, we want to understand the policy of general practices, and showing the social function of his actually ideology. Jayme Portella is considered as one of the greatest exponents of the "linha -dura (hard-line) , the research seeks to explain details about this historical current military, which has in "castelismo" the counterpoint s main and coup d'état of 1964, as founding myth. Investigated the way that general conceives his conception about the conspiracy and consolidation of military autocracy in Brazil and e stablishing the links from their concrete ideology under history